The Linguistic Heritage of Colonial Practice - Weber, Brigitte (Koloniale und postkoloniale Linguistik ;, 2019)
The contributions of this volume offer both a diachronic and synchronic approach to aspects relating to different areas of colonial life as for example colonial place-naming in a comparative perspective. They comprise topics of diverse interests within the field of language and colonialism and represent the linguistic fields of sociolinguistics, onomastics, historical linguistics, language contact, obsolescence convergence and divergence, (colonial) discourse, lexicography and creolistics.